Antiphospholipid antibodies in end‐stage renal disease: A systematic review and meta‐analysis. Issue 3 (10th June 2020) - Ames, Paul R. J.; Merashli, Mira; Bucci, Tommaso; Pastori, Daniele; Pignatelli, Pasquale; Violi, Francesco; Bellizzi, Vincenzo; Arcaro, Alessia; Gentile, Fabrizio
Abstract : Introduction: The relationship between autoimmune hemolytic anemia and antiphospholipid antibodies (aPL) and/or antiphospholipid syndrome has never been systematically addressed. Methods: Systematic review of EMBASE and PubMed databases performed according to PRISMA guidelines from inception to March 2020; meta‐analysis performed by Peto's odds ratio for rare events. Findings: Forty‐five studies with different outcomes met the inclusion/exclusion criteria. The pooled prevalence (PP) of IgG anticardiolipin antibodies (aCL) positivity was greater in end‐stage renal disease (ESRD) than controls (20.2% vs. 2.6%, P = 0.001, I 2 >80%; I 2 = heterogeneity), particularly in hemodialysis patients (18.3% vs. 8%, I 2 = 0%). The PP of lupus anticoagulant was greater in ESRD than controls (8.7% vs. 0.2%, P < 0.0001, I 2 = 0%). The standardized mean difference of IgG aCL favored ESRD rather than controls ( P < 0.0001, I 2 =97%). The PP of fistula occlusion was greater in IgG aCL‐positive patients than negative patients (39% vs. 27%, I 2 =97%); the PP of IgG aCL positivity was greater in patients with fistula occlusion than without fistula occlusion (26.9% vs. 23.2%, P = 0.01, I 2 =72%); the same applied to the PP of lupus anticoagulant positivity (23% vs. 0.3%, P < 0.0001, I 2 = 0%). The standardized mean difference of IgG aCL favored fistula occlusion ( P = 0.004, I 2 = 91%). Discussion: Lupus anticoagulant relates to ESRD regardless of management whereas IgG aCL relates specifically to ESRD on hemodialysis, but only lupus anticoagulant associates with fistula occlusion. The expression of aPL as patients positive for aPL rather than as titers precludes further assumptions on the relationship.